Efficacy of Infrainguinal vs Suprainguinal Approach to Fascia Iliaca Compartment Block for Postoperative Analgesia in Patients with Proximal Femoral Fracture: A Randomised Clinical Study - K Jubairiya; Pk Farha; Neera Valsan; Moona; Paul O Raphael; Aj Sukanya Prince Mary; P Anusree; Sm Mohammed Nabeel (Journal of Clinical and Diagnostic Research)
Introduction: The Fascia Iliaca Compartment Block (FICB) has been useful in postoperative pain management for surgeries involving the hip joint and femur. Under ultrasound guidance, one can approach this compartment using either the conventional infrainguinal or suprainguinal methods. The suprainguinal approach was expected to be better due to the more proximal placement of the drug. Aim: To compare the suprainguinal and infrainguinal approaches to FICB for postoperative analgesia in proximal femur fractures. Materials and Methods: This unicentric prospective randomised double-blind clinical study was conducted over six months following approval from the ethics committee and in accordance with the Clinical Trial Registry of India (CTRI/2022/12/048121). A total of 60 patients were randomly divided into two groups of 30 using computer-generated random numbers. FICB was performed in the preoperative area with either approach under ultrasound guidance depending on the assigned group. Surgery was performed under a subarachnoid block after 30 minutes. Postoperative pain was assessed using the Visual Analogue Scale (VAS) score. If the VAS score was greater than 4, rescue analgesia was administered with intravenous paracetamol 1 gm infusion. The incidence of postoperative delirium was also recorded. Results: The duration of postoperative analgesia was significantly longer in the suprainguinal group (Group S) (481.7±136.7 minutes) compared to the infrainguinal group (Group I) (385.2±99.39 minutes) (p-value=0.001). The VAS score was similar between the groups at 2, 6, and 12 hours. However, the VAS score was significantly lower in Group S (2.333±0.479) compared to Group I (2.867±1.196) at 24 hours. The incidence of postoperative delirium was comparable in both groups (p-value=0.754). Conclusion: Regarding the duration of analgesia and reduced pain intensity at 24 hours, suprainguinal FICB was more effective than infrainguinal FICB in managing pain. There were no significant differences in overall paracetamol intake and the incidence of delirium between the two groups.